Exploring the Potential of Ribes nigrum L., Aronia melanocarpa (Michx.) Elliott, and Sambucus nigra L. Fruit Polyphenol-Rich Composition and Metformin Synergy in Type 2 Diabetes Management - Katarzyna Zima; Barbara Khaidakov; Laura Banaszkiewicz; Krzysztof Lemke; Paulina Karolina Kowalczyk (Journal of Diabetes Research)
Type 2 diabetes, characterized by insulin resistance and impaired glucose homeostasis, is commonly managed through lifestyle interventions and medications such as metformin. Although metformin is generally well-tolerated, it may cause gastrointestinal adverse effects and, in rare cases, precipitate lactic acidosis, necessitating cautious use in individuals with renal dysfunction. Additionally, concerns regarding its impact on hepatic function have led to its discontinuation in cirrhotic patients. This study explores the potential synergistic benefits of a polyphenol-rich blend containing black currant, chokeberry, and black elderberry extracts alongside metformin in managing type 2 diabetes. In vitro results highlighted distinct effects of AMPK pathway modulation, showcasing reductions in cholesterol and triglyceride levels alongside a notable enhancement in glucose uptake. The blend, when combined with metformin, significantly reduced insulin levels and fasting glucose concentrations in an in vivo model. Furthermore, hepatic analyses unveiled a modulation in cellular pathways, suggesting a potential influence on lipid metabolism, attenuation of inflammatory pathways, a decrease in cellular stress response, and antioxidant defense mechanisms, collectively implying a potential reduction in liver fat accumulation. The findings suggest a potential complementary role of polyphenols in enhancing the efficacy of metformin, possibly allowing for reduced metformin dosage and mitigating its side effects. Further clinical studies are warranted to validate these findings and establish the safety and efficacy of this nutraceutical approach in managing type 2 diabetes.